Evaluation of a complex healthcare intervention to increase smoking cessation in pregnant women: interrupted time series analysis with economic evaluation. Issue 1 (15th February 2017) - Bell, Ruth; Glinianaia, Svetlana V; Waal, Zelda van der; Close, Andrew; Moloney, Eoin; Jones, Susan; Araújo-Soares, Vera; Hamilton, Sharon; Milne, Eugene MG; Shucksmith, Janet; Vale, Luke; Willmore, Martyn; et al.
Abstract : Objectives: To evaluate the effectiveness of a complex intervention to improve referral and treatment of pregnant smokers in routine practice, and to assess the incremental costs to the National Health Service (NHS) per additional woman quitting smoking. Design: Interrupted time series analysis of routine data before and after introducing the intervention, within-study economic evaluation. Setting: Eight acute NHS hospital trusts and 12 local authority areas in North East England. Participants: 37 726 records of singleton delivery including 10 594 to mothers classified as smoking during pregnancy. Interventions: A package of measures implemented in trusts and smoking cessation services, aimed at increasing the proportion of pregnant smokers quitting during pregnancy, comprising skills training for healthcare and smoking cessation staff; universal carbon monoxide monitoring with routine opt-out referral for smoking cessation support; provision of carbon monoxide monitors and supporting materials; and an explicit referral pathway and follow-up protocol. Main outcome measures: Referrals to smoking cessation services; probability of quitting smoking during pregnancy; additional costs to health services; incremental cost per additional woman quitting. Results: After introduction of the intervention, the referral rate increased more than twofold (incidence rate ratio=2.47, 95% CI 2.16 to 2.81) and the probability of quitting by delivery increased (adjusted OR=1.81, 95% CI 1.54 to 2.12). The additional cost per delivery was £31 and the incremental cost per additional quit was £952; 31 pregnant women needed to be treated for each additional quitter. Conclusions: The implementation of a system-wide complex healthcare intervention was associated with significant increase in rates of quitting by delivery.